Lagochilascaris minor (Nematoda, Ascarididae) in a domestic cat in a coastal city of the state of São Paulo - Cardoso, Catarina Borges [UNESP]; das Neves, José Henrique; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2020)
This paper describes the discovery of Lagochilascaris minor parasitizing a stray cat (Felis catus) in São Sebastião, a coastal city in the state of São Paulo, Brazil. The cat presented fistulas with purulent secretion in the ventral cervical region. A thorough evaluation revealed nematodes in the site. The parasites were removed, amounting to a total of about 100 specimens. The parasite species was identified based on measurements and morphological characteristics of adult worms. This report of parasitism by L. minor in domestic cats in the state of São Paulo reinforces the need for greater attention to this parasitosis, given the increase in cases among carnivores in Brazil.
Keywords: Feline; Lagochilascaris minor; Parasitic zoonosis